Pengaruh Kombinasi Pemupukan Terhadap Pertumbuhan Pisang Kepok Kuning (Musa acuminata × M. balbisiana) Pada Lahan Kering di Banyumas, Jawa Tengah - Saktiyono Sigit Tri Pamungkas (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2015)
Kepok Kuning banana (Musa acuminate × M.balbisiana) is a banana which has a good adaptability tothe water shortage conditions. The banana has cultivatedin watershed of Tajum river, Banyumas. The place haspotential to be centre of Yellow Kepok banana productionbut the farmers occasionally applied fertilizer unbalancedwhich effect to productivity and quality of banana. It isnecessary to examine proportion of fertilizers to determinethe effective and effi cient fertilizer composition whichincreased productivity and quality of banana.The experiment was conducted on Gentawangi dryland farm, Jatilawang, Banyumas on January-June 2009. Theexperiment was laid out in randomized block design with12 replications and involving single factor. It consistedof 5 treatments The Banana was planted in pattern 3 m x3 m. Results showed that banana required both of organicfertilizers and inorganic in vegetative stage. The treatmentof Urea 150 g + 100 g + SP36 compost 10 kg/tree/applicationshowed the effi cient compared to other, followed bytreatment of ZA 150 g + SP36 KCl 150 g + 50 g/tree/application. Combination of Urea and ZA without organicfertilizer indicated uneffi cient compared to others